Influence of multiphase fillers on mechanical, transport and rheological properties of polypropylene. (2018) - Rasana, N.; Malavika, D.; Aparna, R.; Deepak, T.; Haritha, P.S.; Jayanarayanan, K.
Abstract: Recently increasing importance has been paid to nano level reinforcements in composites as they can significantly improve the properties at very low level of loading. This study is focused to detail the synergistic effect of micro (glass fibre) and nano (nanosilica) fillers in polypropylene (PP) matrix. A significant increase of 26% in the tensile strength and a notable increase in storage modulus and complex viscosity was observed for the hybrid composite. It is seen that the network structure developed by the localization of nanosilica around glass fiber in PP matrix offered an exigent path for solvent penetration.